2019
DOI: 10.1080/17482631.2019.1598722
|View full text |Cite
|
Sign up to set email alerts
|

Towards the contributing factors for stress confronting Chinese PhD students

Abstract: Purpose: A review of literature reveals that stress is prevalent among PhD students who are experiencing higher levels of stress than age-matched general population normative data, and has drawn attention worldwide. However, few studies have examined the factors influencing the psychological well-being of Chinese PhD students and the type of supports most needed. Method: This study was conducted by a qualitative method employing the Grounded Theory. Through purposive sampling, 10 Chinese PhD students were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…“I am green with envy and stressful when I see my classmates at college are well-settled down in their career while I am still struggling for a PhD , my career still being an illusion” (Doctoral researcher, China—[ 49 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…“I am green with envy and stressful when I see my classmates at college are well-settled down in their career while I am still struggling for a PhD , my career still being an illusion” (Doctoral researcher, China—[ 49 ]).…”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that the views of researchers who have experienced difficulties with their mental health or well-being may arguably be more prevalent across the included papers (and thus, more represented in our analysis), as these experiences may make them more inclined to participate in research exploring these concepts [ 48 ]. Similarly, some of the included papers specifically sought out participants with symptoms of a mental health difficulty [ 39 ], and others specifically focused on examining more negative constructs which could contribute to poorer mental health and well-being, such as stress [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that men are more likely to participate in sports than women. The same situation also exists in college students [ 22 ].…”
Section: Introductionmentioning
confidence: 81%
“…As explained by an HR informant, the strategy was to spot those who would have many papers published. Unlike the domestic programmes which had made journal publication mandatory for PhD students (Wang et al, 2019 ), the overseas institutions often left it for their students to decide whether or when they would like to publish their research. Hence, in disciplines where research publication took time, it would be strategic to “save” the publication for later.…”
Section: Methodsmentioning
confidence: 99%
“…With China becoming a more experienced exporter of international students, Chinese students who plan to study abroad have been better informed to prepare for a smoother experience than their predecessors. Meanwhile, their domestically trained peers may have to spend longer time in the programme for reasons such as unemployability and institutional barriers against graduation (Wang et al, 2019 ), hence a reduced age disparity. This and related emerging trends warrant further research on how the hypothesised competition scenario plays out in the real world.…”
Section: Introductionmentioning
confidence: 99%